From Policy to Practice: Interpreting Polish Strategic Culture Amidst the Russian Full-Scale Invasion of Ukraine - Komarnytskyy, Mykhaylo (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
This research analyses the key components of the Polish strategic culture, mainly the national historical memory of previous relations with Russia, the role of NATO in Poland’s security and defence, the country’s objective to become a leading power in the Central and Eastern European, and the concept of strategic culture can become an additional explanatory determinant of Poland’s response to the Russian full-scale aggression against Ukraine. The case study considered Poland’s immediate firm and sweeping support of Ukraine in the first year of the Russian full-scale aggression. This article aims to understand essential determinants in modern Polish foreign and security policy and how they played out during the Russian war against Ukraine. The paper applies the strategic culture as an example of the critical theoretical approach to explain how historically-based context and specific national identical features influence decision-making in present times. The study used a systemic review of related literature, media coverage of the latest Russian war against Ukraine developments, and deductive analysis methods. The central assumption is that the concept of strategic culture becomes a crucial explanatory factor in understanding policy- and decision-making processes in the field of foreign and security policy. The main conclusions of the paper are that Poland’s response and reaction to Russia’s invasion of Ukraine is a continuation of the long-lasting policy maintained by Poland regarding the elimination of military and hybrid threats posed by Russia, reduction of Russian influence in Europe, development of the Eastern European region and strengthening relations with its staunch ally – the US. Prezentowany artykuł analizuje, w jaki sposób kultura strategiczna kształtuje politykę zagraniczną i bezpieczeństwa. Przykładem empirycznym wykorzystanym w badaniach jest polityka zagraniczna i bezpieczeństwa Polski oraz analiza wpływu położenia geopolitycznego, tożsamości narodowej, doświadczenia historycznego i pamięci na zachowania państwa. Studium przypadku rozpatrywane w niniejszej pracy to wpływ pełnoskalowej inwazji Rosji na Ukrainę na politykę zagraniczną i bezpieczeństwa Polski. Celem artykułu jest zrozumienie, które determinanty są najważniejsze we współczesnej polskiej polityce zagranicznej oraz jak cele polityki zagranicznej i bezpieczeństwa są ze sobą powiązane. Celami badania są decyzje polityczne i inicjatywy podejmowane przez Polskę w ostatnich latach oraz podejście strategiczne prezentowane w narodowych dokumentach strategicznych. W pracy zastosowano kulturę strategiczną jako przykład krytycznego podejścia teoretycznego w celu wyjaśnienia, jak historycznie uwarunkowany kontekst wpływa na podejmowanie decyzji. W opracowaniu wykorzystano systemowy przegląd literatury pokrewnej i przekazów medialnych dotyczących najnowszych wydarzeń w wojnie rosyjsko-ukraińskiej, a także metody analizy dedukcyjnej. Głównym założeniem jest to, że wojna rosyjsko-ukraińska wzmacnia międzynarodową markę Polski jako wytrwałego i niezawodnego sojusznika na forach bilateralnych i euroatlantyckich. Głównym wnioskiem płynącym z artykułu jest to, że odpowiedź Polski na inwazję Rosji na Ukrainę jest kontynuacją długoletniej polityki prowadzonej przez Polskę w zakresie eliminacji militarnych i hybrydowych zagrożeń ze strony Rosji, ograniczania wpływów rosyjskich w Europie, rozwoju regionu Europy Wschodniej oraz wzmacniania relacji ze swoim zaufanym sojusznikiem – USA.
Inwazja Rosji na Ukrainę i jej wpływ na politykę zagraniczną Polski
Keywords: Poland’s foreign and security policy; Russian full-scale invasion of Ukraine; strategic culture; polityka zagraniczna i bezpieczeństwa Polski; wojna rosyjsko-ukraińska; kultura strategiczna; tożsamość narodowa